A system for increasing variability in filamentous fungi? - R. Bonatelli Jr.; J. L. Azevedo (Fungal Genetics Reports, 1992)
The possibility of genetic analysis in the Fungi Imperfecti had its origin with the description of genetic recombination without sexual reproduction, later designated the parasexual cycle, in the ascomycete Aspergillus nidulans (Pontecorvo et al. 1953. Adv. Genet. 5:141-238; Pontecorvo 1956. Ann. Rev. Microbiol. 10:393-400). As the description occurred in a species with sexual reproduction, it obviously allowed comparisons between data obtained from sexual and parasexual analysis. Therefore it was possible to establish the basic parameters of genetic analysis far more easily that would have been possible if the parasexual cycle had been discovered in an imperfect species.